Open Data and the Maturity of Tourism Public Service Governance: Evidence from Palutungan - Nanang Suparman (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Open data has become increasingly important for strengthening tourism public service management, yet its practical integration at micro-destination level remains underexplored. This study aims to analyze the maturity of open data-based tourism public service management in the Palutungan/Cisantana tourism area of Kuningan Regency. The study is grounded in Open Government Data Maturity, Public Service Logic, and Smart Tourism Destination perspectives. A qualitative-evaluative case study design was applied through document analysis, digital observation of official tourism and open data platforms, and semi-structured interviews with relevant stakeholders. The findings show that tourism data are available through KuninganBeu, Open Data of Kuningan Regency, BPS-Statistics, and regional planning documents, but remain descriptive, fragmented, and weakly connected to service evaluation, visitor flow management, complaint handling, and operational decision-making. The study concludes that Palutungan/Cisantana is at a developing maturity level, requiring stronger metadata, data integration, and service-oriented governance for sustainable, accountable, and evidence-based destination service improvement.